Analyzing Precipitation Trends in the Cholistan Desert, Pakistan: A Statistical and GIS-Based Study - Haider, Shamsheir; Haq, Fazlul; G. Mark, Bryan (Geographica Pannonica, 2024)
Climate change is driving significant shifts in temperature and precipitation patterns globally, with far-reaching socio-economic and environmental impacts, especially in arid regions. This study examines precipitation variability and long-term trends from 1980 to 2020 in Pakistan's Cholistan Desert, a region where water scarcity poses critical challenges for local communities and ecosystems. Using data from five meteorological stations, we applied a combination of Geographic Information System (GIS) techniques and statistical analyses to assess both seasonal fluctuations and annual trends in precipitation. The results reveal notable spatial variability in precipitation trends across the Cholistan Desert. Positive trends, indicating increased precipitation over time, were observed in the northwestern areas, particularly at the Bhagla, Khanpur, and Fort Abbas stations. In contrast, significant negative trends were detected in the southwestern areas, represented by the DinGarh and MaujGarh stations, where precipitation has steadily decreased over the study period. These contrasting trends reveal the diverse impacts of climate change within the desert pointing out the areas that may face heightened water scarcity. The ongoing shifts in precipitation necessitate targeted water management and climate adaptation strategies to address the challenges posed by these shifting precipitation patterns. For areas with declining trends, strategies focused on rainwater harvesting and conservation will be critical. Regions experiencing increased precipitation may require infrastructure improvements to manage and store water more effectively.
Keywords: desert precipitation variability; Mann–Kendall trend test; Sen Slope Estimator; arid environment; Cholistan Desert